NELSON’S SYNDROME: PATHOPHYSIOLOGY, DIAGNOSIS, AND MANAGEMENT STRATEGIES - Fayziyeva Nozima Gulomovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Nelson’s Syndrome (NS) is a rare but serious complication arising after bilateral adrenalectomy (BA) in patients with Cushing’s disease. The progressive enlargement of a pituitary adenoma and excessive secretion of adrenocorticotropic hormone (ACTH), which can lead to hyperpigmentation, visual disturbances, and potentially life-threatening complications characterize this condition. Despite advances in endocrine surgery and pituitary imaging, NS remains a diagnostic and therapeutic challenge. This article reviews the current understanding of the pathophysiology of NS, presents clinical findings from recent studies, evaluates diagnostic criteria, and discusses treatment options including surgery, radiotherapy, and medical therapy. The study also proposes recommendations for early detection and prevention strategies to minimize the development of NS post-adrenalectomy.